2015
DOI: 10.1163/22134808-00002496
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity, and Its Limits, in Adult Human Primary Visual Cortex

Abstract: Article:Haak, Koen V, Morland, Antony B orcid.org/0000-0002-6754-5545 and Engel, Stephen A (2015) Plasticity, and Its Limits, in Adult Human Primary Visual Cortex. Multisensory Research. 297-307. ISSN 2213-4808 https://doi.org/10.1163/22134808-00002496 eprints@whiterose.ac.uk https://eprints.whiterose.ac.uk/ Reuse Unless indicated otherwise, fulltext items are protected by copyright with all rights reserved. The copyright exception in section 29 of the Copyright, Designs and Patents Act 1988 allows the maki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 67 publications
(64 reference statements)
1
14
1
Order By: Relevance
“…The specific mechanisms that underlie representational drift remain elusive, but it was suggested that drift may be an inevitable outcome of the network dynamics in deep brain circuits that consist of multiple input and output loops (Rule, O’Leary and Harvey, 2019). Consistent with this logic, and given the need to support stable perception and motor outputs, it is plausible that brain circuits situated closer to the sensory input or to the motor output will display highly stable neuronal representations (Haak, Morland and Engel, 2015; Haak and Mesik, 2016).…”
Section: Introductionmentioning
confidence: 92%
“…The specific mechanisms that underlie representational drift remain elusive, but it was suggested that drift may be an inevitable outcome of the network dynamics in deep brain circuits that consist of multiple input and output loops (Rule, O’Leary and Harvey, 2019). Consistent with this logic, and given the need to support stable perception and motor outputs, it is plausible that brain circuits situated closer to the sensory input or to the motor output will display highly stable neuronal representations (Haak, Morland and Engel, 2015; Haak and Mesik, 2016).…”
Section: Introductionmentioning
confidence: 92%
“…This process, termed cortical reorganisation, is perhaps the most extreme form of brain plasticity. According to these early studies, however, reorganisation is much more restricted in the adult brain: adult cats subjected to visual occlusion did not exhibit the same deficits and cortical changes as did kittens [3] (see [4] and [5] for related evidence in monkeys and humans; see [6] for current debate on the adult’s visual cortex capacity for reorganisation).…”
Section: Plasticity In Sensory Cortical Topographiesmentioning
confidence: 99%
“…As far as the modeling confound is concerned, failing to factor in the absence of input when the stimulus falls within the scotoma biases receptive field estimates in a way that closely mimics the expected effects of cortical reorganization (Binda et al 2013, Haak et al 2015). All the neurophysiological (Kaas et al 1990, Gilbert and Wiesel 1992, Darian-Smith and Gilbert 1995, Abe et al 2015) and fMRI (Baseler et al 2011, Ferreira et al 2017) studies that did find shifts in retinal organization in V1 used methods susceptible to this modeling confound.…”
Section: Adult Plasticitymentioning
confidence: 99%